SPIRITUALITY AND STUDENTS: NEW DIRECTIONS OF EDUCATION UNDER THE INFLUENCE OF STATE DECISIONS, MODERN TEACHER COMPETENCES AND PEDAGOGICAL INNOVATIONS (World Bulletin of Physical Education and Sports Science, 2025)
This article analyzes the current issues of developing spirituality in the modern education system and the impact of state policy, pedagogical innovations and artificial intelligence technologies on the spiritual development of students. The article also discusses the professional, moral and digital competencies of a modern teacher and the theoretical and methodological foundations of instilling national values in a digital educational environment based on a scientific approach.
Keywords: Spirituality, students, state policy, teacher competence, pedagogical innovations, artificial intelligence, digital transformation, spiritual education.